A novel method for determining human ex vivo submaximal skeletal muscle mitochondrial function - Hey‐Mogensen, Martin; Gram, Martin; Jensen, Martin Borch; Lund, Michael Taulo; Hansen, Christina Neigaard; Scheibye‐Knudsen, Morten; Bohr, Vilhelm A.; Dela, Flemming (The Journal of physiology, 2015)
Key points The present study utilized a novel method aiming to investigate mitochondrial function in human skeletal muscle at submaximal levels and at a predefined membrane potential. The effect of age and training status was investigated using a cross‐sectional design. Ageing was found to be related to decreased leak regardless of training status. Increased training status was associated with increased mitochondrial hydrogen peroxide emission. Despite numerous studies, there is no consensus about whether mitochondrial function is altered with increased age. The novelty of the present study is the determination of mitochondrial function at submaximal activity rates, which is more physiologically relevant than the ex vivo functionality protocols used previously. Muscle biopsies were taken from 64 old or young male subjects (aged 60–70 or 20–30 years). Aged subjects were recruited as trained or untrained. Muscle biopsies were used for the isolation of mitochondria and subsequent measurements of DNA repair, anti‐oxidant capacity and mitochondrial protein levels (complexes I–V). Mitochondrial function was determined by simultaneous measurement of oxygen consumption, membrane potential and hydrogen peroxide emission using pyruvate + malate (PM) or succinate + rotenone (SR) as substrates. Proton leak was lower in aged subjects when determined at the same membrane potential and was unaffected by training status. State 3 respiration was lower in aged untrained subjects. This effect, however, was alleviated in aged trained subjects. H2O2 emission with PM was higher in aged subjects, and was exacerbated by training, although it was not changed when using SR. However, with a higher manganese superoxide dismuthase content, the trained aged subjects may actually have lower or similar mitochondrial superoxide emission compared to the untrained subjects. We conclude that ageing and the physical activity level in aged subjects are both related to changes in the intrinsic functionality of the mitochondrion in skeletal muscle. Both of these changes could be important factors in determining the metabolic health of the aged skeletal muscle cell.